Analysis of the dynamic effect of the electrical interconnection on the stability of the rotor angle for synchronous generators in the electric power system of Syria - A. Alzakkar; N. P. Mestnikov; F. Alhajj Hassan; I. M. Valeev (Известия высших учебных заведений: Проблемы энергетики)
This article focuses on the study and analysis of the importance of interconnections between electricity systems, which increases with greater probability due to the dependence of all countries and States on electricity and the ease of its transfer between countries in order to supplement their economic and technical benefits. THE PURPOSE. This study analyzes the dynamic impact of interconnection on circuit stability for synchronous generators in Syrian power grids. In addition, the authors of the article analyzed the dynamic effect of interaction on the stability of the angle of rotation of the rotor of synchronous generators operated in the Syrian power system through the use of dynamic modeling of the country's power system. METHODS. In the course of the study, the authors used a technique based on the dynamic representation of the power system and the construction of its nonlinear equations, followed by the use of the PSS ® E program. 230-400 kV.RESULTS. The authors of the article obtained a solution and determination of the system parameters and the separation time of the boundaries of three-phase short circuits in a 400 kV network in addition to determining the angular position of the generator circuits, and thus, its stability was checked, regardless of whether it works independently in the electric power system of Syria or is part of a network. CONCLUSION. In the course of the study, the authors obtained the following conclusions, such as: an increase in CFCT was found for generating units in the power system of Syria due to connection activation, an increase in transmitted power, which leads to an increase in the stabilization zone after a failure and before the start of connecting electrical systems to the country's power system, as well as it is necessary to conduct in-depth dynamic studies of the entire system in order to represent the effect of the connection on the parameters of the system, taking into account the increase in power.